An integrated observation dataset of the hydrological-thermal deformation in permafrost slopes and engineering infrastructure in the Qinghai-Tibet Engineering Corridor - Luo, Lihui (Copernicus Publications, 2021)
An integrated observation dataset of the hydrological-thermal deformation in permafrost slopes and engineering infrastructure in the Qinghai-Tibet Engineering Corridor: Across the Qinghai-Tibet Plateau (QTP) there is a narrow engineering corridor with widely distributed slopes, called the Qinghai-Tibet Engineering Corridor (QTEC), where a variety of important infrastructures are concentrated. These facilities are transportation routes for people, materials, energy, etc., from mainland China to Tibet. From Golmud to Lhasa, the engineering corridor covers 632 km of permafrost containing the densely occurring Qinghai-Tibet Railway and Highway as well as power/communication towers. Slope failure in permafrost regions, caused by permafrost degradation, ground ice melting, etc., affects the engineering construction and permafrost environments in the QTEC. We implement a variety of sensors to monitor the hydrological-thermal deformation between permafrost slopes and permafrost engineering projects in the corridor. In addition to soil temperature and moisture sensors, the global navigation satellite system (GNSS), terrestrial laser scanning (TLS), and unmanned aerial vehicles (UAVs) were adopted to monitor the spatial distribution and changes in thermal deformation. An integrated dataset of hydrological-thermal deformation in permafrost engineering and slopes in the QTEC from the 1950s to 2020, including meteorological and ground observations, TLS point cloud data, and RGB and thermal infrared (TIR) images, can be of great value for estimating the hydrological-thermal impact and stability between engineering and slopes under the influence of climate change and engineering disturbance. The dataset and code were uploaded to the Zenodo repository. Image credits: Map data © 2021 Google, Data 10, NOAA, U.S, Navy, NGA, GEBCO, Image IBCAO. - Map data © 2021 Google, Maxar Technologies, CNES/Airbus.